Pengembangan Bahan Ajar Digital Menggunakan Heyzine Flipbook untuk Meningkatkan Motivasi Belajar Peserta Didik pada Materi Gotong Royong di Lingkungan Sekitar - Chrysanda Alya Zahra; Mira Mirawati; Fitri Anjaswuri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Development of Digital Instructional Materials Using Heyzine Flipbook to Improve Students’ Learning Motivation on the Topic of Mutual Cooperation in the Surrounding Environment. Students' learning motivation in the topic of Mutual Cooperation in the Surrounding Environment was found to be relatively low. Based on the results of the initial classroom observations, this condition was indicated by students' low enthusiasm during the learning process, the limited use of digital teaching materials, and the predominance of conventional teaching methods. Therefore, this study aimed to develop digital teaching materials using heyzine flipbook and examine their feasibility and effectiveness for elementary school learning. This study employed the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research subjects consisted of 36 fifth-grade students of SD Negeri Kracak 01, selected using a random sampling technique. The research instruments included expert validation sheets (content, language, and media), teacher and student response questionnaires, and a learning motivation questionnaire. The validation results showed average scores of 98% from the content expert, 86% from the language expert, and 98% from the media expert, indicating that the product was highly feasible. The limited field trial showed teacher responses of 98% and student responses of 88.6%, both categorized as highly practical. The N-Gain analysis yielded an average score of 0.71, which falls into the high category. Therefore, the digital teaching materials developed using heyzine flipbook were found to be feasible, practical, and effective in improving the learning motivation of fifth-grade students at SD Negeri Kracak 01.